2012
DOI: 10.1371/journal.pone.0045755
|View full text |Cite
|
Sign up to set email alerts
|

ROC Generated Thresholds for Field-Assessed Aerobic Fitness Related to Body Size and Cardiometabolic Risk in Schoolchildren

Abstract: Objectives1. to investigate whether 20 m multi-stage shuttle run performance (20mSRT), an indirect measure of aerobic fitness, could discriminate between healthy and overweight status in 9–10.9 yr old schoolchildren using Receiver Operating Characteristic (ROC) analysis; 2. Investigate if cardiometabolic risk differed by aerobic fitness group by applying the ROC cut point to a second, cross-sectional cohort.DesignAnalysis of cross-sectional data.Participants16,619 9–10.9 year old participants from SportsLinx p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
47
7

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(62 citation statements)
references
References 17 publications
(25 reference statements)
8
47
7
Order By: Relevance
“…Interestingly, the observed cut-off levels for cardiorespiratory fitness obtained in adolescents participating in the HELENA study are similar to those published previously by other studies conducted in past generations of children and adolescents from the USA9 and different European countries8 10 11 12 13 with diverse environmental, cultural and social factors. Of note is that previous studies used less comprehensive health indices than the one used in the present study and did not use behaviour-related components.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Interestingly, the observed cut-off levels for cardiorespiratory fitness obtained in adolescents participating in the HELENA study are similar to those published previously by other studies conducted in past generations of children and adolescents from the USA9 and different European countries8 10 11 12 13 with diverse environmental, cultural and social factors. Of note is that previous studies used less comprehensive health indices than the one used in the present study and did not use behaviour-related components.…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, they showed that boys who met the fitness levels were between four and five times more likely to have a low CVD risk compared with those who did not meet the standards. Comparable results were found (i) in 4500 children and adolescents from Denmark, Estonia, Norway and Portugal, who were tested as part of the European Youth Heart Study (EYHS);10 (ii) in 16 619 English children from the SportsLinx Project11 and (iii) in 450 Portuguese adolescents 13. All the aforementioned studies calculated mathematically the cardiorespiratory fitness levels associated with a more favourable cardiovascular profile, which turned out to be similar to the health-related cardiorespiratory fitness thresholds suggested by worldwide recognised organisations such as the European Group of Pediatric Work Physiology5 or the Cooper Institute for Aerobics Research6 7 (table 3).…”
Section: Discussionmentioning
confidence: 93%
“…When our data were compared to European (IDEFICS) and the East of England Healthy Hearts Study reference data (14,49) using z scores, there were no meaningful differences in physical fitness parameters between the children in our study and the age-and sexmatched reference populations (z scores shown in Table 1). Table 3 details study level and participant characteristics from our investigation and other contemporary English data sets where data were available (1,6,10,11,35,37,40). As publicly available raw data were not available for English data other than from East of England Healthy Hearts Study, further statistical comparisons of physical fitness parameters via z scores were not possible.…”
Section: Comparisons With Other English Regionsmentioning
confidence: 99%
“…When aerobic fitness is defined as mass-related VO 2peak, there appears to very little historic change in young people's aerobic fitness (4). Conversely, when the term is operationalized as maximal field-based endurance running performance (eg, 20-m shuttle run test [20mSRT] performance), the global picture is one of decreasing levels for several decades (4,6,33,41,44,46,50). This public health problem is of particular concern in England, with data from some regions indicating that aerobic fitness performance specifically is declining by around 8% per decade (36,41)-twice the rate observed in other developed nations (45).…”
mentioning
confidence: 99%
See 1 more Smart Citation